Thoracic Synovial Cyst at the Th2-3 Level Causing Myelopathy - Martin M. Sundskarð; Shahin Gaini (Case Reports in Neurological Medicine, 2017)
Intraspinal synovial cyst is a rare cause of myelopathy. These cysts present most often in the lumbar and cervical parts of the spine but are more infrequent in the thoracic spine. We present a case of a 73-year-old man with an intraspinal, extradural synovial cyst at the Th2-3 level causing paraesthesia and weakness in the legs. A laminectomy and excision of the cyst were performed and the patient recovered fully. In the thoracic spine, synovial cysts are almost exclusively found in the lower part. Laminectomy, with excision, is the treatment of choice, although steroid injections have been described.